2013
DOI: 10.1002/pon.3339
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for and experiences of family involvement in cancer treatment decision‐making: patient–caregiver dyads study

Abstract: Most patients and family caregivers valued and expected family involvement in TDM. However, there is little explicit agreement in regard to which party in the dyad should take decisional leadership and who should play a supporting role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
125
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 38 publications
11
125
2
1
Order By: Relevance
“…16, 11, 26 Our study extends this work by revealing that the decision support network for newly diagnosed breast cancer patients is larger than previously understood. In fact, we found that the majority of breast cancer patients reported having large networks, defined in this study as having 3 or more informal DSPs, and we further discovered that these supporters often included family members and friends beyond just their partners or spouses.…”
Section: Discussionsupporting
confidence: 76%
“…16, 11, 26 Our study extends this work by revealing that the decision support network for newly diagnosed breast cancer patients is larger than previously understood. In fact, we found that the majority of breast cancer patients reported having large networks, defined in this study as having 3 or more informal DSPs, and we further discovered that these supporters often included family members and friends beyond just their partners or spouses.…”
Section: Discussionsupporting
confidence: 76%
“…15 Family members in such countries tend to believe that TDM should lie in the hands of the patient's family members and that these individuals should be involved directly in the TDM process, perhaps due to a strong sense of moral responsibility. 7,16 In certain Middle Eastern, North African and South Asian societies, the family has final authority in TDM, as often the patient is inseparably linked to the family as a whole. 17 For example, the majority of cancer patients in South Korea preferred shared TDM with their family members, although it was noted that there may be disagreements between family members and patients.…”
mentioning
confidence: 99%
“…5,6 In another study of patient-caregiver dyads in Korea, most patients and caregivers valued and expected family involvement in TDM; however, there was little explicit agreement regarding which party in the dyad should take decisional leadership and which should play a supporting role. 7 Several studies have shown that cancer patients and their family members prefer family participation in TDM to some extent. [7][8][9] Among patients with advanced lung cancer in Belgium, Pardon et al reported that patients' family members regularly attended consultation and treatment appointments in order to provide emotional support, request further information and participate in the TDM process.…”
mentioning
confidence: 99%
See 2 more Smart Citations